Molecule-based materials : the structural network approach - Ohrstrom, Lars (Elsevier, 2005)
The properties of a material depend not only on the specific atoms and molecules it contains, but also on the arrangement of these in space. Many of these three-dimensional arrangements are described as "3D-nets" or "3D-networks". Molecule-Based Materials: The Structural Network Approach is about the synthesis, description, nomenclature and analysis of such nets and the relation of the nets to the physical properties of the materials. It introduces the mathematics, and includes a short guide to programs useful for retrieving, analysing and naming nets. Complete with illustrations and examples of coordination polymer and hydrogen bonded nets, this unique easy-to-read book examines all aspects of 3D nets and will undeniably prove itself valuable to newcomers, well-seasoned students and researchers working in crystallography, inorganic or organic chemistry. * Covers all aspects of molecule-based 3D nets, complete with 3D illustrations * Contains summary tables of all nets * Easy reading eliminates the need for background knowledge in crystallography or mathematics